2014
DOI: 10.1590/0104-1169.3538.2464
|View full text |Cite
|
Sign up to set email alerts
|

Pre-frailty and frailty of elderly residents in a municipality with a low Human Development Index

Abstract: OBJECTIVE: to identify the prevalence of the factors associated with pre-frailty and frailty of elderly residents in a municipality with a low Human Development Index METHOD: Cross-sectional study with a populational and household framework conducted with 316 elderly people. Frailty was determined from the presence of three or more of the following factors: (i) self-reported unintentional weight loss; (ii) lack of strength and energy; (iii) weakness; (iv) slowness; (v) low level of physical activity. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
(25 reference statements)
2
13
0
4
Order By: Relevance
“…No studies were found that evaluated the fragility from the Clinical-Functional Vulnerability Index-20 in the elderly participants assisted by the family health strategy. However, in national and international studies that used other screening instruments for the fragility in the elderly people and in cities with low human development index (12)(13) , the indices revealed were similar to the data evidenced in this study, with a high prevalence of fragile elderly people with advancing age and female gender.…”
Section: Discussionsupporting
confidence: 87%
“…No studies were found that evaluated the fragility from the Clinical-Functional Vulnerability Index-20 in the elderly participants assisted by the family health strategy. However, in national and international studies that used other screening instruments for the fragility in the elderly people and in cities with low human development index (12)(13) , the indices revealed were similar to the data evidenced in this study, with a high prevalence of fragile elderly people with advancing age and female gender.…”
Section: Discussionsupporting
confidence: 87%
“…Quase metade das pessoas idosas por nós avaliadas apresentava pré-fragilidade. Esta condição atingiu a maioria dos idosos rastreados na comunidade em investigações de natureza similar (Duarte & Paúl, 2015;Júnior et al, 2014;Lenardt et al, 2016;Pegorari & Tavares, 2014). Tais resultados colocam importantes desafios às políticas de saúde e envelhecimento ativo, já que com o avançar da idade aumenta a probabilidade destas pessoas transitarem para frágeis (Apóstolo et al, 2017;Xue, 2011 (Collard et al, 2012;Fried et al, 2001;Santos-Eggimann et al, 2009).…”
Section: Discussionunclassified
“…Torna-se pois importante que as pessoas idosas corrijam os problemas auditivos através de adequada vigilância médica e uso de próteses; recomendação extensível aos problemas de visão e deglutição. A perceção do estado de saúde associou-se à condição de fragilidade, corroborando investigações prévias (Júnior et al, 2014). A literatura enfatiza que os idosos fragilizados apresentam menor qualidade de vida relacionada com a saúde e alta prevalência de doenças crónicas (Lenardt et al, 2016;Strandberg et al, 2011).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Data appear to indicate that both under and overweight could lead to situations of frailty and bidirectionality which were also outlined in previous studies. 3,25 This suggests that the association between BMI/frailty may go both ways, one related to low weight and sarcopenia and the other with sarcopenic obesity.…”
Section: Discussionmentioning
confidence: 99%